POLITENESS STRATEGIES IN ENOLA HOLMES 2 MOVIE SCRIPT - Imama, Fitria Mafaizatul; Shofiyuddin, Muh (Journal Albion : Journal of English Literature, Language, and Culture, 2024)
ABSTRACTThis research aims to describe language politeness strategies in the film “The Enola Holmes Mysteries” directed by Harry Bradbeer on Netflix. This research focuses on the principles of language politeness using the theory of Geoffrey Leech's six maxims, namely wisdom, generosity, respect, simplicity, consensus, and sympathy. The method used in this research is descriptive qualitative with four steps data collection, data reduction, data display, and drawing conclusion. The object of study is film. The data are the transcribed subtitles of the film's main characters and supporting characters in the form of text. This research results revealed that there are 397 data on positive (40%), 304 data on bald (30%), 286 data on negative (29%), and 14 data on off-record (1%). In addition, the film's dominant strategy is a positive strategy that includes both speaker and listener, marking identity, seeks agreement, asserts that speakers know and care about listeners' wants, avoids agreement, is optimistic, promises, satisfies listeners to show understanding, assumes or assert reciprocity in the activity of communication, and assumes or assert reciprocity.Keywords: Politeness strategies, Politeness types, Enola Holmes 2